Electromagnetic and Thermal Design/Analysis of an Induction Motor for Electric Vehicles - Ulu, Cenk; Kömürgöz Kırış, Güven; Korman, Oğuz (EJournal Publishing, 2019)
© 2019 Int. J. Mech. Eng. Rob. Res.The most commonly used electrical machine is the induction machine since it is durable, easy to manufacture and control. Additionally, it requires less maintenance, and responses different loads. In this study, the design of 115kW (continuous 85kW) squirrel cage induction motor is presented for electric vehicle applications. Main design constraints and performance criteria of the motor are determined and depending on these values, computer aided design is performed. In the design procedure, initially, an analytical design of the electric vehicle motor is performed depending on specified design criteria. Then, the analytical design is verified by using finite element analysis. Depending on the obtained results in electromagnetic analyses, the squirrel cage induction motor is modified in order to improve the obtained performance further. The electromagnetic and thermal analyses of the designed motor are performed by using Maxwell® and ANSYS software programs, respectively. Designed motor will stand maximum allowable temperature based on temperature rise of the used insulation class. The analyses results show that the designed motor satisfies the design criteria.